Ultrasound Characteristics of Myometrial Invasion in Endometrial Carcinoma: A Prospective Cohort Study - Anis Cerovac; Dubravko Habek; Zlatko Hrgović (IMR Press, 2024)
Background: Both objective and subjective transvaginal sonography (TVS) methods are used to assess the degree of myometrial invasion (MI). Subjective TVS assessment of MI (<50% or >50%) may be as good or better than any objective measurement technique. The aim of this study is to examine the ultrasound characteristics of endometrial cancer (EC) in two groups of patients; with myometrial invasion less and greater than 50%. Methods: This is a prospective cohort study included 60 female patients with pathohistologically (PHD) proven endometrial cancer. Patients were divided into two groups, after surgery and PHD assessment of MI degree, into those with less and more than 50% MI. The degree of MI was performed by subjective assessment (<50% and >50%). Results: The frequency of anteroposterior (AP) diameter of EC greater than 2 cm was statistically significantly higher in the group of subjects with MI >50% (p < 0.00001). The volume of EC in the group of patients with MI >50% is statistically significantly higher, with a difference of 10.48 milliliters compared to the group of subjects with MI <50% (p < 0.00014). The difference in the average distance of the EC from the serosa is 0.11 cm between the two examined groups and is statistically significant (p = 0.0394). The kappa concordance coefficient for the subjective TVS method versus the PHD finding was statistically significant (p < 0.001), and was kappa = 0.72. Analysis of the diagnostic accuracy showed that the subjective TVS method compared to the gold standard in the diagnosis of MI >50% has a good diagnostic value: accuracy = 0.87; sensitivity = 0.77; specificity = 0.94; positive predictive value = 0.91; negative predictive value = 0.84; positive likelihood ratio = 13.08; negative likelihood ratio = 0.25. According to the subjective method of TVS, the degree of MI was overestimated in 5.9% of respondents, underestimated in 23.1%. Conclusions: The three dimensions, as well as the volume of endometrial cancer, obtained by TVS, are significantly higher in subjects with >50% myometrial invasion; there is also a significantly higher frequency of EC diameter greater than 2 cm in the group of subjects with >50% myometrial invasion.